2008
DOI: 10.7326/0003-4819-149-6-200809160-00003
|View full text |Cite
|
Sign up to set email alerts
|

Massage Therapy versus Simple Touch to Improve Pain and Mood in Patients with Advanced Cancer

Abstract: BACKGROUND Small studies of variable quality suggest that massage therapy may relieve pain and other symptoms. OBJECTIVE Evaluate efficacy of massage for decreasing pain and symptom distress and improving quality of life among persons with advanced cancer. DESIGN Multi-site randomized clinical trial. SETTING Population-based Palliative Care Research Network (PoPCRN). PATIENTS 380 adults with advanced cancer experiencing moderate-severe pain; 90% were enrolled in hospice. INTERVENTION Six 30-minute ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
268
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(284 citation statements)
references
References 64 publications
7
268
1
8
Order By: Relevance
“…These data confirm the safety of massage for patients with advanced cancer. 19 Massage therapists were instructed to record any reason that required them to stop the 30-minute treatment session early. In the 814 encounters there were only 13 notations (1.6%) of early termination.…”
Section: Adverse Events and Treatment Terminationmentioning
confidence: 99%
“…These data confirm the safety of massage for patients with advanced cancer. 19 Massage therapists were instructed to record any reason that required them to stop the 30-minute treatment session early. In the 814 encounters there were only 13 notations (1.6%) of early termination.…”
Section: Adverse Events and Treatment Terminationmentioning
confidence: 99%
“…The massage was superior to the simple-touch [21], while the aromatic manual massage superimposed the manual massage with oil, with important effect in reducing pain and depressive symptoms [22].…”
Section: Additional Therapies (N= 2)mentioning
confidence: 97%
“…The first study compared single-touch massage [21], the second compared the aromatic manual massage to general manual massage with oil, noting its effect on pain, anxiety, depression and life quality in patients with advanced cancer and palliative care [22]. The massage was superior to the simple-touch [21], while the aromatic manual massage superimposed the manual massage with oil, with important effect in reducing pain and depressive symptoms [22].…”
Section: Additional Therapies (N= 2)mentioning
confidence: 99%
“…The effects of urut Melayu can be classified into physical, psychologic, and effects on daily living activities. One patient said: All the patients expressed their wish to possibly get urut Melayu more frequently as the urut made them feel ringan [relaxed, refreshed, rejuvenated, and re-energized; feeling of replenished energy] 8 . More than half of the patients reported that other people too had noticed that they had markedly improved following urut Melayu.…”
Section: Patients' Assessment Of Urut Melayumentioning
confidence: 99%